MOVIE WAR STRATEGY ACCIDENT"TJOET NJA DHIEN" IN SEMIOTIC AESTHETIC STUDY - Maksalmina (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
The film Tjoet Nja Dhien has emerged as a pivotal element in Indonesian cultural and historical research, yet an in-depth examination of its use of semiotic aesthetics within the context of war remains underdeveloped.This research endeavors to address this lacuna by exploring the application of semiotic aesthetics in depicting war strategy accidents within the visual narrative of Tjoet Nja Dhien.Research Questions: First, the question of the catalyst for the war strategy accident is investigated. Second, the significance of the symbolic and aesthetic messages in the film is examined.This research employs a qualitative method to identify the depiction of war strategy accidents in the film and to explore the symbolic meaning and aesthetic messages contained in it through semiotic aesthetic analysis.The research methodology involves literature study and movie observation. The findings reveal that the depiction of the war strategy accident in the film is characterized by the internal and external conflicts experienced by the primary character. This is manifested through the utilization of visual symbols such as fire, ruins, and battlefield landscapes.From an aesthetic perspective, semiotic elements are employed to enhance the narrative, including lighting techniques that symbolize inner struggles, as well as the use of dialog and background sounds that underscore the values of struggle and sacrifice. The symbolic message of the film underscores the duality between physical and spiritual struggle, while also representing Aceh's cultural resilience in the face of colonialism.This research contributes to Indonesian film studies by enriching the understanding of the representation of war in a cultural context and by maintaining and respecting the historical values contained in the film "Tjoet Nja Dhien."